CREATIVE CHARACTER EDUCATION IN THE UTILIZATION OF USED GOODS INTO VERTICULTURE IN CLASS IV SD N 7 KUTOSARI KEBUMEN - Susiani, Tri Saptuti; Khanasah, Noviatun (Social, Humanities, and Educational Studies (SHES): Conference Series, 2018)
Humans use goods and services to meet the needs every day increasing. One alternative in overcoming this is to recycle used goods. Through creative character education for students class four of SD N 7 Kutosari by utilizing used items to become verticultur. The method used in this study is the stage of action research. The results of this study showed a significant increase in the first cycle shorting trash be based on his species and the second cycle showed the high creativity of students in the use of used plastic bottles as verticultur.